A systematic decision-making approach for the assessment of hybrid renewable energy applications with techno-economic optimization: Application to the Rajamangala University of Technology Srivijaya (Trang Campus), Southern Thailand - Weerasak Chaichan; Jompob Waewsak; Yves Gagnon (Songklanakarin Journal of Science and Technology (SJST), 2021)
This paper proposes a systematic decision-making approach for the assessment of hybrid renewable energy applications with techno-economic optimization, with application to the Rajamangala University of Technology Srivijaya (Trang Campus) in southern Thailand. Using the hybrid optimization model for electric renewable (HOMER) Pro simulation tool, the techno-economic aspects of a grid-connected combined solar photovoltaics, wind turbine generator, and energy storage (Li-Ion battery), are optimized in order to minimize the net present cost (NPC) and the levelized cost of energy (LCOE). The model inputs are NASA-Surface Meteorology and Solar Energy and Modern-Era Retrospective analysis for Research and Applications databases, and monthly power loads of the campus analyzed. The results are compared and optimized amongst four combinations. It is found that the optimal hybrid renewable energy power system offers the lowest NPC and the lowest LCOE to satisfy the full load of the campus.